2017
DOI: 10.1038/s41598-017-07144-5
|View full text |Cite
|
Sign up to set email alerts
|

A cancer stem cell model as the point of origin of cancer-associated fibroblasts in tumor microenvironment

Abstract: Cancer-associated fibroblasts (CAFs) are one of the most prominent cell types in the stromal compartment of the tumor microenvironment. CAFs support multiple aspects of cancer progression, including tumor initiation, invasion, and metastasis. The heterogeneous nature of the stromal microenvironment is attributed to the multiple sources from which the cells in this compartment originate. The present study provides the first evidence that cancer stem cells (CSCs) are one of the key sources of CAFs in the tumor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
118
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 147 publications
(121 citation statements)
references
References 27 publications
3
118
0
Order By: Relevance
“…CAFs affect cancer cell growth through cell-cell interactions and the secretion of various invasive molecules, such as cytokines, chemokines, and inflammatory mediators. [477][478][479] CAFs in the TME play an indispensable role in the generation and maintenance of CSCs. 480 CAFs transform cancer cells into CSCs.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%
“…CAFs affect cancer cell growth through cell-cell interactions and the secretion of various invasive molecules, such as cytokines, chemokines, and inflammatory mediators. [477][478][479] CAFs in the TME play an indispensable role in the generation and maintenance of CSCs. 480 CAFs transform cancer cells into CSCs.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%
“…In the same context, the accumulated data show that CSCs have the ability to differentiate into multi-lineage, such as pericytes, endothelial cells, and cancer-associated fibroblasts, and they have the potential to reconstruct their microenvironment by differentiation or recruitment of other cells and, therefore, contribute to the initiation and progression of cancers [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…CM mimics the cancerous niche, in which miPSCs are exposed to different growth factors and chemokines secreted from cancer cells. While using this method, we successfully generated CSC models using CM from lung, pancreas, breast, and liver cancer cell lines [12,[17][18][19][20]. Furthermore, we showed that our CSC models could differentiate into vascular endothelial-like cells and cancer-associated fibroblasts, which support tumor growth in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have correlated expression of CSC ( CD44, ALDH1A1, NOTCH1 ) and Epithelial Mesenchymal Transition (EMT) ( CADHERIN, TWIST, TGF‐βeta, MMPs) markers with the process of invasion and metastasis . Additionally, microenvironment is known to be a major player in maintaining CSC properties in different cancers . Factors released from cancer associated fibroblasts (CAF), such as chondroitin‐sulfate, proteoglycan‐serglycin, promotes tumor growth, invasion, migration and colonisation in breast and lung cancers in CD44‐dependent manner .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Additionally, microenvironment is known to be a major player in maintaining CSC properties in different cancers. [16][17][18] Factors released from cancer associated fibroblasts (CAF), such as chondroitin-sulfate, proteoglycan-serglycin, promotes tumor growth, invasion, migration and colonisation in breast and lung cancers in CD44-dependent manner. 19 Co-culture of stromal cells such as omental adipose derived and/or bone-marrow mesenchymal stem cells with tumor associated macrophages have been correlated with aberrant expression of stem cell profile in ovarian, myeloma, breast, and gastric cancer cells.…”
Section: Introductionmentioning
confidence: 99%